Book Review: The Less People Know about Us - Tiyani Rodrigo (Journal of Financial Therapy, 2020)
The Less People Know about Us is an autobiographical book written by Axton Betz-Hamilton. The book focuses on her own experiences of child identity theft and the elder financial exploitation perpetrated by a loved one. Inspired by this experience, Dr. Betz-Hamilton went on to receive a Ph.D. in Human Development and Family Studies and has since dedicated her research to the area of child identity theft. This book review evaluates the organization of the book exploring the usability of the book for practitioners in the field of financial therapy. The Less People Know about Us was enjoyable to read due to the use of simple language and short chapters which allows the readers to viscerally experience the emotions and experiences of a victim of identity theft perpetrated by a family member.
Keywords: book review